Changing Levels of Bloom's Taxonomy in Learning Objectives and Exam Questions in First-Semester Introductory Chemistry before and during Adoption of Guided Inquiry - Eileen M. Kowalski; Carolann Koleci; Kenneth J. McDonald (MDPI AG, 2024)
When General Chemistry at West Point switched from interactive lectures to guided inquiry, it provided an opportunity to examine what was expected of students in classrooms and on assessments. Learning objectives and questions on mid-term exams for four semesters of General Chemistry I (two traditional semesters and two guided inquiry semesters) were analyzed by the Cognitive Process and Knowledge dimensions of Bloom's revised taxonomy. The results of this comparison showed the learning objectives for the guided inquiry semesters had a higher proportion of Conceptual and Understand with a corresponding decrease of Factual, Procedural, Remember and Apply learning objectives. On mid-term exams, the proportion of Remember, Understand, Analyze/Evaluate, Factual, and Conceptual questions increased. We found that guided inquiry learning objectives and mid-term exam questions are more conceptual than traditional courses and may help explain how active learning improves equity in introductory chemistry.